Jamrach's Menagerie (Melbourne Text Publishing, 2011)
London, 1857: after surviving an encounter with an escaped tiger on the streets of Bermondsey, nine-year-old Jaffy stumbles into a job for its owner, the wild animal collector, Mr Jamrach.Commissioned by Jamrach to find and collect a sea dragon, Jaf soon joins a ship bound for the South Seas, and so begins a wonder-filled voyage of discovery. But when things start to go awry, Jaf's journey becomes a fight for survival which will push faith, love and friendship to their outermost limits. Brilliantly written and utterly compulsive, Carol Birch's novel evokes the smells, sights and flavours of the nineteenth century from the squalor of London to the islands of the South Seas